GOOD GOVERNANCE DALAM PENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KANTOR DESA CANDIMULYO JOMBANG - Sari, Zhelika; Anah, Lik (Perwira Journal of Economics & Business, 2023)
This research was conducted to find out how the implementation of good governance in improving the quality of public services at the Candimulyo village office. This research was conducted in the public service department. The research method that the writer uses is descriptive qualitative and the source of the data is obtained through documentation and literature study with reference to internet media and village RPJM files. The collection technique used by the author is observation, interviews, and documentation. Good governance or good governance has principles that can be applied in the public service system. According to UNDP, the principles are participation, rule of law, openness, responsiveness, consensus- oriented, fairness, effectiveness and efficiency, and strategic vision. At the Candimulyo Village Office there are several principles of Good governance that have been applied, such as the principle of the rule of law, the principle of responsiveness, and the principle of openness. These principles can be a starting point for implementing other good governance principles, so that the quality of public services at the Candimulyo Village Office will be better.